Glenn Kaino - this book is a promise - Markonish, Denise (DelMonico Books/D.A.P., 2021)
Published for the Los Angeles-based interdisciplinary artist Glenn Kaino's largest exhibition to date, In the Light of a Shadow, this book showcases his work and how art can chronicle parallel trajectories of disparate political and geographical contexts, utilizing history to speak about our present, and art to facilitate political action and hope. Kaino has built his career in the space between these two; creating projects that are based on the magic of trust, fair promises and righting the lapses in memory and omissions of history. This Book Is a Promise is organized in a galaxy-like structure, with different aspects of Kaino's production over the years represented as intertwined constellations. Additionally, the book reads in two directions, Memory and Promise, each with its own cover. The Memory side presents a retrospective survey, while the Promise surveys the MASS MoCA exhibition. Themes explored include equity, visibility, belief, regeneration and space-making.
Wendebuch
Keywords: Kaino, Glenn -- 1972-; Kaino, Glenn / (Glenn Akira) / 1972- / Exhibitions; Kaino, Glenn / (Glenn Akira) / 1972-; Exhibition catalogs; Ausstellungskatalog -- Massachusetts Museum of Contemporary Art -- 05.04.2021-05.09.2022 -- North Adams, Mass.; Bildband